Vítimas do trânsito em São José do Rio Preto, São Paulo - Santos, Marilene Rocha dos (2004)
In order to characterize the victims of traffic accidents occurring in the perimeter of the city of São José do Rio Preto, state of São Paulo, 2,267 victims were analyzed. This group covered registered victims: in the Bulletins of Occurrence of the Military Police (BO); in Death Certificate up to 180 days from the accident; in local newspaper hospitals. The victims were characterized, according to variables that allowed to know the characteristics of the accidents, the epidemiological profile, the care provided, the lesions presented and evolution, the average cost of hospital care and costing sources, georeferencing of the places of occurrence of the accidents, and such as the evaluation of the coverage and the quality of the data obtained in the different sources ... The georeferencing of the accident sites indicates the avenues and highways as generators of victims for the main categories and the highest rate of victims per square kilometer. Regarding the coverage and quality of the data, 39% of the victims were not registered in BO and the majority of the hospital records did not have an annotation of the circumstances of the accident.